Financing the global environment - Peter Nunnenkamp (Intereconomics, 1993)
The international coordination of environmental protection is particularly difficult with regard to developing countries. How can the industrialized countries be persuaded that financial compensation to the developing countries is economically justified? How can external support for the developing countries be organized so that the incentives for environmental protection are strengthened effectively?
Keywords: 330; Umweltpolitik